Convergent and Discriminant Validity of the Five Factor Form - Rojas, Stephanie L.; Widiger, Thomas A. (Assessment (Odessa, Fla.), 2014)
The current study tests the convergent and discriminant validity of a modified version of the Five Factor Model Rating Form (FFMRF), a one-page, brief measure of the five-factor model. The Five Factor Form (FFF) explicitly identifies maladaptive variants for both poles of each of the 30 facets of the FFMRF. The purpose of the current study was to test empirically whether this modified version still provides a valid assessment of the FFM, as well as to compare its validity as a measure of the FFM to other brief FFM measures. Two independent samples of 510 and 330 community adults were sampled, one third of whom had a history of some form of mental health treatment. The FFF was compared with three abbreviated and/or brief measures of the FFM (i.e., the FFMRF, the Ten Item Personality Inventory, and the Big Five Inventory), a more extended measure (i.e., International Personality Item Pool-NEO), an alternative measure of general personality (i.e., the HEXACO-Personality Inventory-Revised), and a measure of maladaptive personality functioning (i.e., the Personality Inventory for Diagnostic and Statistical Manual of Mental Disorders, 5th edition). The results of the current study demonstrated convergent and discriminant validity, even at the single-item facet level.